A Certainty Eqivalent Approach to Municipal Bond Default Risk Estimation - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1991)
This paper extends the risk-neutrality default model of municipal bonds to consider the effect of risk aversion on the estimation of default probability. A model is proposed to separate the default risk assessment from the investor's risk aversion. Empirical results show that the risk-neutrality model consistently overestimates the default probability but that the magnitude of this overestimate is generally small and statistically insignificant.